PENGEMBANGAN KORELASI SEDERHANA PROSES PEMISAHAN SISTEM DUA FASA MINYAK DAN AIR DI SEPARATOR BERDASARKAN METODE SAYDA DAN TAYLOR - Hendriwibowo, Novan
Background of this research is that threre are several conditions of fields where the sizes of separators are too large at the late stage of production. It is hypothezed that there is a need to develop a new paradigm in the design of the separator by considering the production forecats so that the size of separator not too large when the production has declined, in this case by developing a simple correlation. This research is conducted with an intent to obtain a simple correlation of optimum two phase oil-water separators design by considering the dynamic production and to know parameters that affect the optimization of water production. Optimization of water production in separator of field X is done by using a horizontal separator model that was developed by Sayda and Taylor. Production data in this study are taken from a reservoir simulation results of field X and literature data. The results show that fluid flow rate, length and radius of separator are very significant on the oil and water separation process. It is proved that the optimum size for this field separator would follow the equation Log(L)= -0.983 Log(r) + 0.526 With the help of a software, this research produces a simple correlation that can be applied to other fields by considering the most important factor in the oil and water separation process. The equation is Log (L) = - 1.49 - 0.581 Log (r) + 0.536 Log(Qliq)